Efficacy of high-dose cytarabine and aclarubicin in combination with G-CSF regimen compared to intermediate/high-dose cytarabine and standard-dose cytarabine induction regimen for non-remission acute myeloid leukemia - Lei, Meiqing; Liu, Limin; Wang, Zhiming; Wu, Depei (Indian journal of cancer, 2019)
BACKGROUND: Acute myeloid leukemia (AML) patients with non-remission (NR) after the first cycle of standard induction chemotherapy remain a challenge owing to poor response and tolerance to re-induction regimen. We retrospectively evaluated the efficacy and safety of three regimens in AML patients refractory to the first course of standard induction regimen. MATERIALS AND METHODS: The three regimens consisted of (1) High-dose cytarabine, aclarubicin and granulocyte colony-stimulating factor (HD-CAG) regimen (n = 44); (2) intermediate/high-dose cytarabine (I/HDAC) regimen (n = 30); and (3) standard-dose cytarabine (SDAC) combination regimen that was identical to the first course of standard induction regimen (n = 27). RESULTS: Results indicated that after the second course, the overall response (OR), i.e., complete remission [CR]+partial remission [PR]) rates in HD-CAG was higher than in the I/HDAC group (84.1% vs. 56.7%, P = 0.009), whereas the CR rates among 3 groups were not statistically different (P = 0.541). Meanwhile, the proportion of subjects reporting certain adverse effects in the HD-CAG group was lower than the I/HDAC or SDAC groups. There were no significant differences in overall survival (OS) and disease-free survival (DFS) rates among the 3 groups (P = 0.881 and P = 0.872, respectively). CONCLUSION: Our preliminary results indicate that HD-CAG regimen may represent a better alternative option for AML patients with NR after the first course of standard induction chemotherapy.